Taxation, Infrastructure, and Endogenous Trade Costs in New Economic Geography - Stefan Gruber; Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
This paper presents a New Economic Geography model with distortionary taxation and endogenized trade costs. Tax revenues finance a public good, infrastructure. We show that the introduction of costly public investment in infrastructure increases agglomerative tendencies. With respect to the regions' sizes, in the periphery, the price-index for manufacturing goods decreases, whereas for the core, the price-index is rather high since the distortionary effect of taxes dominates. 'Free riding' or, in terms of regional policy, externally funded infrastructure investment; is beneficial for the periphery, which can devote all its tax revenue to local demand support, generating a positive home market effect and driving the catch-up process.
Keywords: F12; H25; H54; R12; 330; Neue ökonomische Geographie; Transportkosten; Steuer; Infrastrukturinvestition; Regionalpolitik